Within-season changes in habitat use of forest-dwelling boreal bats - Vasko V; Blomberg AS; Vesterinen EJ; Suominen KM; Ruokolainen L; Brommer JE; Norrdahl K; Niemelä P; Laine VN; Santangeli A; Lilley TM (WILEY, 2022)
Bats utilize forests as roosting sites and feeding areas. However, it has not been documented how bats utilize these habitats in the boreal zone with methods afforded by recent technological advances. Forest structure and management practices can create a variety of three-dimensional habitats for organisms capable of flight, such as bats. Here, we study the presence of boreal bats in a forest forming a mosaic of different age classes, dominant tree species, canopy cover, soil fertility, and other environmental variables, throughout their active season in the summer using passive ultrasound detectors. Our results indicate a preference for mature forest by Eptesicus nilssonii and a pooled set of Myotis bats. Both groups of bats also showed temporal changes in their habitat use regarding forest age. In June and July, both groups occurred more often in mature than young forests, but from August onwards, the difference in occurrence became less evident in Myotis and disappeared completely in E. nilssonii. In addition, E. nilssonii was more often present in forests with low canopy cover, and its occurrence shifted from coniferous forests to deciduous forests during the season. The results reflect the within-season dynamics of bat communities and their ability to utilize different types of forest as environmental conditions change. Yet, the results most importantly emphasize the importance of mature forests to bat diversity and the need to conserve such environments in the boreal zone.